2013 North Carolina Hurricane Workshop Summary - Covi, Michelle P. (My University, 2013)
The North Carolina Division of Emergency Management in collaboration with East Carolina University's Center for Natural Hazards Research held a Hurricane Workshop on May 22, 2013 at the Murphy Center in Greenville, NC. Over 180 emergency managers, meteorologists, emergency responders and university researchers gathered to learn about new policies and procedures for social media, planning and emergency response, modeling storm surge and planning for future flooding emergencies and the experiences from managing Hurricane Sandy in the Northeast.
Keywords: Hurricanes; Emergency management; NCEM; Emergency disaster